Disagreement, Unenforceability, and Harm Reduction - Weinstock, Daniel M. (Health Care Anal, 2020)
Talk of harm reduction has expanded horizontally, to apply to an ever-widening range of policy domains, and vertically, becoming part of official legal and political discourse. This expansion calls for philosophical theorization. What is the best way in which to characterize harm reduction? Does it represent a distinctive ethical position? How is it best morally justified, and what are its moral limits? I distinguish two varieties of harm reduction. One of them, technocratic harm reduction, is premised on the fact of non-enforceability of prohibitionist policies. The second, deliberative harm reduction, is premised on the fact of reasonable disagreement, grounded in the fact that reasonable persons disagree about a range of controversial behaviours. I argue that deliberative harm reduction better accounts for some of harm reduction’s most attractive features, and provides a plausible way of accounting for harm reductions’s justificatory grounds and limits.